Respuestas

  • Usuario de Brainly
2013-04-19T23:02:08+02:00

Solución:

-18x + 15y - 2- [-7x +y-20z -(-10x+30y -25z)]=-18x+15y -2 -[-7x + y-20z+10x-30y+25z]

::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::=-18x+15y-2 -[3x-29y+5z]

::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::=-18x+15y-2-3y+29y-5z

::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::::=-21x+44y-5z-2 <===Respeusta.

 

Espero haberte ayudado con tu ejercicio. Suerte.

Pitagor.

  • Usuario de Brainly
2013-04-19T23:09:49+02:00

-18x+15y-2-[-7x+y-20z+10x-30y+25z]

-18x+15y-2+7x-y+20z-10x+30y-25z

-21x+44y-5z-2

Espero que te sirva